A megújuló energiaforrások alkalmazása a villamosenergia- és hőtermelésre II. : geotermikus energia és biomassza = Application of renewable energy sources to power and heat generation II. : geothermal energy and biomass - Haffner, Tamás (Közép-Európai Közlemények, 2017)
Renewable energy sources can be used to generate electricity, heat energy and combined heat and power. Despite several technological and other barriers, use of renewable energy is constantly growing worldwide thus we can expect further expansion of renewable energy sources and the increase of their importance in energy supply. Geothermal energy means the internal heat present in the Earth’s crust that enables utilization of heat energy and electricity production. There is no example of the latter in Hungary. The internal heat of the Earth is some fifty thousand times the amount of energy obtained from the use of known oil and natural gas reserves. Biomass can be classified based on several criteria; vast majority thereof is formed in the sea, which is used only in an insignificant amount. Further problem of use of biomass is that in addition to energy utilization, it is an important raw material of agriculture and food industry thus its excessive use may lead to major food problems. We can find several examples of both the utilization of geothermal energy and of biomass in Hungary, the operation thereof is illustrated through South-Transdanubia examples in the study.